On the distinctiveness of Amapasaurus, its relationship with Loxopholis Cope 1869, and description of a new genus for L. guianensis and L. hoogmoedi (Gymnophthalmoidea/Ecpleopodini: Squamata) - Pellegrino, Katia Cristina Machado; Brunes, Tuliana Oliveira; Souza, Sergio Marques; Laguna, Marcia Maria; Avila-Pires, Teresa Cristina Sauer; Hoogmoed, Marinus Steven; Rodrigues, Miguel Trefaut (Zootaxa, 2018)
Amapasaurus is a monotypic genus of forest lizards never accessed molecularly and, based on morphological similarities, suggested to be closely related to species of the former Leposoma parietale group Ruibal 1952, currently in the genus Loxopholis Cope 1869. Two other species, formerly allocated in Arthrosaura (A. guianensis and A. hoogmoedi), were tentatively moved to Loxopholis in an extensive molecular revision of Gymnophthalmoidea. Here we add mitochondrial and nuclear sequence data (12S, cyt b, ND4, c-mos and NT3) of Amapasaurus to previously published and new data of all Ecpleopodini genera (except for Adercosaurus), in order to test: i) the close relationship between Amapasaurus and Loxopholis and ii) the position of Loxopholis guianensis and Loxopholis hoogmoedi with three different phylogenetic methods, expanding the knowledge on the current taxonomy of Ecpleopodini. Concatenated analyses of mitochondrial and nuclear data (2303 bp) under Bayesian Inference, Maximum Likelihood and Maximum Parsimony methods recovered a strongly supported sister relationship between Amapasaurus tetradactylus Cunha 1970 and species of Loxopholis. Genetic divergence between Amapasaurus and this assemblage of Loxopholis is high in both mitochondrial ( 18% for cyt b) and nuclear ( 12% for c-mos) regions, supporting its generic distinctiveness. Differing from the current taxonomy of the Ecpleopodini tribe, our analyses recovered Lo. guianensis and Lo. hoogmoedi as a distinct clade that is sister to all other Loxopholis plus Amapasaurus. Supplemented by external and hemipenial morphology data available from the literature along with DNA sequences, we restrict Loxopholis to the species of the former parietale group of Leposoma and describe a new genus to allocate Lo. guianensis and Lo. hoogmoedi.